Enhanced anti-tumor immune responses and delay of tumor development in human epidermal growth factor receptor 2 mice immunized with an immunostimulatory peptide in poly(D, L-lactic-co-glycolic) acid nanoparticles. Issue 1 (December 2015) - Campbell, Diahnn; Saenz, Rebecca; Bharati, Ila; Seible, Daniel; Zhang, Liangfang; Esener, Sadik; Messmer, Bradley; Larsson, Marie; Messmer, Davorka
Abstract Introduction Cancer vaccines have the potential to induce curative anti-tumor immune responses and better adjuvants may improve vaccine efficacy. We have previously shown that Hp91, a peptide derived from the B box domain in high-mobility group box protein 1 (HMGB1), acts as a potent immune adjuvant. Method In this study, Hp91 was tested as part of a therapeutic vaccine against human epidermal growth factor receptor 2 (HER2)-positive breast cancer. Results Free peptide did not significantly augment immune responses but, when delivered in poly(D, L-lactic-co-glycolic) acid nanoparticles (PLGA-NPs), robust activation of dendritic cells (DCs) and increased activation of HER2-specific T cells was observedin vitro . Vaccination of HER2/neu transgenic mice, a mouse breast cancer model that closely mimics the immune modulation and tolerance in some breast cancer patients, with Hp91-loaded PLGA-NPs enhanced the activation of HER2-specific cytotoxic T lymphocyte (CTL) responses, delayed tumor development, and prolonged survival. Conclusions Taken together these findings demonstrate that the delivery of the immunostimulatory peptide Hp91 inside PLGA-NPs enhances the potency of the peptide and efficacy of a breast cancer vaccine.